The intersection of gender and race in older adults' decision to receive COVID-19 vaccines. Issue 1 (4th January 2023) - Shapiro, Janna R.; Privor-Dumm, Lois; Rosser, Erica N.; Leng, Sean X.; Klein, Sabra L.; Morgan, Rosemary
Highlights: Vaccinated older adults were categorized as eager or hesitant compliers (HC). More of the Black participants, particularly women, were characterized as HC. HC perceived risks associated with the vaccines and the system providing them. Sources of hesitation and promoters of vaccination were shaped by race and gender. Abstract: COVID-19 vaccines are essential public health tools for protecting older adults, who are at high risk of severe outcomes associated with COVID-19. Little is known, however, about how older adults approach the decision to receive a COVID-19 vaccine. We hypothesized that intersections between gender and race may provide unique insight into the decision-making process and the factors that lead to vaccine uptake among hesitant individuals. We performed in-depth interviews with 24 older adults who had been vaccinated against COVID-19 and used the framework approach with an intersectional lens to analyze data. Two typologies emerged: eager compliers did not question the need to vaccinate, whereas hesitant compliers were skeptical of the vaccine and underwent a thorough decision-making process prior to vaccination. For eager compliers, the vaccine offered protection from a disease that posed a serious threat, and few risks were perceived. In contrast, hesitant compliers perceived risks associated with the vaccine product or mistrusted the infrastructure that led to rapid vaccine development. Hesitancy was greater among Black participants, and only Black participants reported mistrust in vaccine infrastructure. At the intersection of gender and race, a 'White male effect' was observed, whereby White men perceived the fewest risks associated with the vaccine, and Black women were the most fearful of serious side effects. Nearly all hesitant compliers ultimately got vaccinated due to the threat of COVID-19. Convenient access through vaccine clinics in senior's buildings was pivotal for hesitant compliers and external and internal influences had differential impacts by race and gender. Emphasizing the risk of COVID-19, convenient and accessible opportunities for vaccination, and messages that are targeted to specific groups are likely to increase vaccine uptake among older adults.